2014
DOI: 10.1111/ped.12279
|View full text |Cite
|
Sign up to set email alerts
|

Effect of meropenem with or without immunoglobulin as second‐line therapy for pediatric febrile neutropenia

Abstract: MEPM is effective and safe for second-line treatment of febrile episodes in neutropenic pediatric patients. Moreover, IVIG is effective for patients with low serum IgG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In the first study, we demonstrated that MEPM was effective and safe as second-line treatment for cases refractory to first-line treatment (cefepime or PIPC/TAZ). The findings obtained also indicated that the combination of IVIG in addition to MEPM was slightly more effective in cases with low serum IgG levels (<500 mg/dL) than in those with IgG higher than 500 mg/dL [3]. In the second study, PIPC/TAZ was found to be as effective and safe as MEPM when it was used in second-line treatment for cases refractory to first-line MEPM (approximately 50% of cases with MEPM treatment failure were rescued by PIPC/TAZ and vice versa).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In the first study, we demonstrated that MEPM was effective and safe as second-line treatment for cases refractory to first-line treatment (cefepime or PIPC/TAZ). The findings obtained also indicated that the combination of IVIG in addition to MEPM was slightly more effective in cases with low serum IgG levels (<500 mg/dL) than in those with IgG higher than 500 mg/dL [3]. In the second study, PIPC/TAZ was found to be as effective and safe as MEPM when it was used in second-line treatment for cases refractory to first-line MEPM (approximately 50% of cases with MEPM treatment failure were rescued by PIPC/TAZ and vice versa).…”
Section: Discussionmentioning
confidence: 71%
“…However, limited information is currently available on second-line antibiotic therapy for FN. We previously conducted two prospective studies on second-line antibiotic therapy for FN [3,4]. The first study showed the usefulness of meropenem (MEPM) as second-line antibiotic therapy as well as concomitant intravenous immunoglobulin (IVIG) [3].…”
Section: Introductionmentioning
confidence: 99%